Survival Rates of Colorectal Cancer in Academic Hospital Universitas Gadjah Mada, Yogyakarta: A Cohort Studyada, Yogyakarta: A Cohort Study - Agung Widianto; Wahyu Kartiko Tomo; Nistimara Anugrah Azdy; Renata Uli Aviola; Sekarini Wening Ayu (Academic Hospital Journal, 2026)
Background:  Colorectal cancer (CRC) is the third most common cancer worldwide. It poses a significant challenge to healthcare systems, including those in Indonesia. This study investigates CRC survival rates and their association with prognostic factors at the Academic Hospital Universitas Gadjah Mada (UGM), Yogyakarta.Methods: This is a cohort-retrospective study. All patients who were diagnosed with CRC and treated in the Surgery Division of Academic Hospital UGM from January 2019 to December 2023 were enrolled. Kaplan-Meier survival curves were used to estimate overall survival, and the log-rank test was used to compare overall survival between prognostic groups.Result: The study included 110 patients with CRC. The median follow-up was 713 days. The estimated 1-year overall survival of all CRC patients treated at Academic Hospital UGM was 66.75%. The average Overall Survival (OS) was 752.335 days. Log-rank analysis showed p-values of 0.485, 0.468, 0.437, and < 0.001 for sex, age, cancer stage, and treatment, respectively. Treatment type significantly impacted survival. Patients who underwent surgery alone had a lower OS compared to those treated with surgery plus chemotherapy. Patients who received surgery alone also had 10-fold higher mortality than those who received combination therapy (HR 10.288; CI 95%, 3.603–29.387, p<0.001).Conclusion: Survival outcomes for colorectal cancer patients vary based on sex, age, stage, and treatment type. Surgery combined with chemotherapy was associated with better OS in CRC patients.